Are Latin American performance audits leading to changes?. Issue 3 (21st October 2019) - Yetano, Ana; Torres, Lourdes; Castillejos‐Suastegui, Blanca
Abstract : The purpose of this paper is to analyze the perceptions of the public entities audited in Latin America (the auditees) about the effectiveness of the performance audits carried out on their institutions by their supreme audit institutions (SAIs; the auditors) to determine to what extent these audits are promoting changes in these public entities. After revising the webs of the SAIs of all Latin American countries, a sample of the entities evaluated with performance audits was selected and a questionnaire (focused on the audit process, the actions taken afterwards, and the follow‐up processes) was sent to them. The results show, as in other Organisation for Economic Co‐operation and Development settings, different degrees of real implementation of performance audits in this geographical area. The audited entities that perceive performance audits useful and trust in the SAIs' activities are also those that implement more recommendations and sooner.